2019
DOI: 10.3390/app10010080
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Process of Canola Oil and n-Hexane Mixtures in Dynamic Diesel Engine Operating Conditions

Abstract: The article discusses the problem of using canola oil and n-hexane mixtures in diesel engines with storage tank fuel injection systems (common rail). The tests results of the combustion process in the dynamic operating conditions of an engine powered by these mixtures are presented. On the basis of the conducted considerations, it was found that the addition of n-hexane to canola oil does not change its energy properties and significantly improves physicochemical properties such as the surface tension and visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…This effect can be obtained, for example, by the addition to vegetable fuels of n-hexane (Hex) and ethanol (Et). Taking this into account a series of engine tests in static and dynamic conditions, during which the diesel engine was powered with mixtures of canola oil with the addition of n-hexane were made [21][22][23]. Despite the fact that the addition of n-hexane to canola oil decreased the surface tension, slightly changed the density, and significantly decreased the viscosity of the mixtures, the values for diesel fuel were not obtained [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This effect can be obtained, for example, by the addition to vegetable fuels of n-hexane (Hex) and ethanol (Et). Taking this into account a series of engine tests in static and dynamic conditions, during which the diesel engine was powered with mixtures of canola oil with the addition of n-hexane were made [21][22][23]. Despite the fact that the addition of n-hexane to canola oil decreased the surface tension, slightly changed the density, and significantly decreased the viscosity of the mixtures, the values for diesel fuel were not obtained [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The use of alternative fuels is one of the main solutions currently allowing the reduction of pollutant emissions [10]. Literature information on the subject of the research of various alternative fuels was found, e.g., in [11][12][13][14][15], and about reduction in the consumption of lubricating oils and plastic lubricants [16; 17]. Among others, for economic and rural development reasons, there is a growing interest in plant-derived fuels (biodiesel) [18][19][20] and LPG or CNG gas fuels [9; 10; 15; 21; 22].…”
Section: Introductionmentioning
confidence: 99%
“…Due the environmental challenges, new fuels for internal combustion (IC) engines are still being developed. A lot of studies are focused on renewable fuels such as biodiesel, selected alcohols (ethanol, methanol) as well as plant oils and their mixtures with n-hexane [13]. Additionally, selected ethers, including ethyl tert-butyl ether [7] and diethyl ether, are considered as possible fuels for diesel engines [6,8].…”
Section: Introductionmentioning
confidence: 99%